Reduksi Bijih Besi Lampung Memanfaatkan Reduktor Gas Produser Model Hasil Gasifikasi Biomassa [Reduction of Lampung Iron Ore Using Producer Gas Model Reductor] - Suharto (Jurnal Metalurgi, 2019)
The producer gas model from the biomass waste gasification was utilized as reduction in the iron ore reduction process. A mixture of gases containing CO, H2, CH4, CO2, CnHm, and N2 was used as a producer gas model for reducing the Lampung iron ore, which hematite as the primary mineral content. Iron ore is prepared up to sizes -6+3 mm and -12+10 mm, and then to be reduced in the vertical tube furnace at a temperature variation of 800, 900 and 1000 °C, and a reduction time of 45, 60 and 75 minutes, respectively. The percentage of Fe and metallization were observed at various temperatures, reduction times, and the size of the iron ore. The reduction of iron ore of a size of -6+3 mm at a temperature of 1000 °C during 75 minutes yielded the highest percentage of Fe and metallization of 67.36% and 84.25%, respectively. Image-J analysis depicted than iron ore of a size of -6+3 mm had a greater amount of porosity (39.48%) than the porosity of the size of the iron ore size -12+10 mm. The XRD analysis results show that the highest content of Fe metal (highest peak) was obtained from samples of -6+3 mm at temperatures and reduction times of 1000 °C and 75 minutes, respectively. Producer gas from gasification is expected to be employed as an iron ore reduction actually in an effort to substitute coal and natural gas.